A effectiveness of technical indicators - a study on cnx it indices - K, Prabhakaran; S, Nagarajan (Journal of Management and Science, 2012)
There are numerous technical tools available to predict future trend of index prices. All tools may not be effective for all the companies and at all times. The purpose of this study is to find out the effectiveness of technical tools in predicting the index price movement. The research is based on secondary data collected from various websites. The data is collected for two different time periods representing the bullish and bearish seasons. The technical indicators taken for the study are Relative Strength Index (RSI), Money Flow Index (MFI) and On Balance Volume (OBV). From the study it is found that Relative Strength Index, Money Flow Index and On Bonus Volume are effective in predicting the index movement CNX IT during the Bullish period and during the Bearish period, Stochastic Oscillator isdeemed effective.